Model Latihan Pencak Silat Berbasis Analisis Biomekanika Kinovea Untuk Meningkatkan Efektivitas Tendangan Siswa SMP - Adek Arifin Harahap; Budi Valianto; M. Irfan; Rahma Dewi; Amir Supriadi (Jurnal Sporta Saintika, 2025)
The effectiveness of pencak silat kicks in junior high school students remains low due to limitations of conventional training methods that neglect biomechanical analysis. This study aimed to develop and test a pencak silat training model based on biomechanical analysis using Kinovea application to improve kick effectiveness. The research employed Borg & Gall's Research and Development (R&D) method with 40 extracurricular pencak silat students from three schools in Medan. Development included 10 progressive biomechanical drills integrated with Kinovea video analysis to provide visual augmented feedback. Expert validation results showed product feasibility of 91.1% (very feasible category), practicality test of 85.8% (very good category), and effectiveness test using paired-sample t-test demonstrated kick scores increased from 44.25 (pre-test) to 79.85 (post-test) with a difference of 35.60 points (t = 43.82; p = 0.000; Cohen's d = 9.48; N-Gain = 0.64). This model proved valid, practical, and effective as an affordable technology-based training innovation for school pencak silat development.